UTILIZING GEOGEBRA FOR SOLVING ECONOMIC MATHEMATICS PROBLEMS: PROMOTING LOGICAL REASONING IN PROBLEM-BASED LEARNING - Warsitasari, Wahyu Dwi; Rofiki, Imam (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Logical reasoning is very important to be used by as the basis of creative activities such as creating or applying mathematical concepts in the real world. By implementing Problem-Based Learning (PBL) with GeoGebra's assistance, logical reasoning abilities can be developed. This research intends to investigate the effect of utilizing GeoGebra to support PBL on students' capacity for logical reasoning while addressing economic mathematics problems. This study employed a quantitative method with one group pretest-posttest quasi-experimental research design. GeoGebra was used in classroom instruction as part of the PBL model to help students solve economic math problems logically. Following the implementation of PBL with the aid of GeoGebra, it may be inferred that there are disparities in students' capacities for logical reasoning based on the non-parametric statistical test of the Wilcoxon test. These findings demonstrate that using GeoGebra in collaboration with problem-based learning improves students' capacity for logical reasoning. GeoGebra-assisted PBL is recommended to be used as a medium to assist students in developing logical reasoning in solving economic mathematics problems.